Plan estratégico de comunicación de la imagen corporativa de PREFACERO - Espinosa Andrade, Paulina Karina (2012)
Organizational communications are essential to coordinate efforts oriented to achieve goals pursued by a company. A very important aim of communications is to establish high-quality relationships between an organization and its publics. Such relationships provide companies with social notoriety and with an image adequate to its ends and activities. In the context of organizational communications, corporate image plays a fundamental role in the perception of a given company by its different publics. Besides offering high-quality products, companies of the steel industry that strive to maintain themselves in the market, need to build a solid image that translates into trust and loyalty from the clients. According to the latter, the present work attempts to design an image positioning strategy that differentiates PREFACERO (a company of the metallurgical sector) from other competing organizations. In order to do this, a number of evaluation procedures were conducted (interviews, field observations, and theoretical research). In a subsequent stage, in consistency with the results an intervention strategy was outline